Estudo e desenvolvimento de metodologia de dosagem de argamassa estrutural auto adensável - Thiago Ferreira Barbosa (2016)
The civil construction market has demanded increasingly efficient and standardized procedures that allow the industrialization of the segment. Currently there are few methods of dosing and execution of self-compacting and high strength mortars, which makes it difficult to standardize their production. The objective of this work is to develop a methodology for the dosing of self-compacting structural mortar with a focus on precast structures, allowing its production in a standardized way, taking into account all the desired parameters, validating this methodology and evaluating the properties of the mortar produced. For the validation, natural sand, Portland cement CP-V, limestone powder and ViscoCrete 20 HE superplasticizer were used for the production of mortars using the methodology developed. The following tests were performed to obtain the properties for evaluation of mortars: mini-cone slump test, mini v-funnel test, fresh and hardened mass density, water absorption index, porosity, dynamic modulus of elasticity, axial compression strength, carbonation, electrical resistivity and digital microscope image. The work proposes the determination of the dosage in an experimental way, according to the materials used. It is also proposed to replace part of the cement by addition, reducing the production cost of the mixture and the environmental impacts. It is concluded that the method is efficient, effective and of low complexity execution, which allows it to be replicated in laboratories, factories and construction sites. The data are obtained with a reliability of 95% (t test)